Customer Segmentation with AI-Based Customer Relationship Management for Effective Marketing of Nichoa Chocolate MSMEs - Andi Balqis Mutiara Asizah; Valentino Aris; Andika Isma; Masud; Andi Aisyiah Rahmatillah (Global Research and Collaboration, 2026)
This study aims to design and evaluate an AI-integrated Customer Relationship Management (CRM) application to support marketing decision-making at Nichoa Chocolate SMEs. Initial problems include inconsistent customer data recording, transactions that are not yet connected to analytics, limited data dashboards, and the absence of customer segmentation, resulting in marketing strategies that tend to be unsuitable for business needs. The system was developed using a Research and Development approach based on the ADDIE model. The built system integrates transaction data with RFM analysis to generate measurable customer mapping and more targeted marketing strategy recommendations. The analysis results showed that the recency value was dominated by new and nearly lost customer segments, so the recommended strategy emphasised a retention-first approach through the reactivation of passive customers, regular communication, and personalised offers, accompanied by efforts to convert new customers to make repeat purchases. The system evaluation showed that all functional test scenarios were successful, usability was rated as good through demonstrations and interviews, and the application performance was very high. These findings confirm that AI-integrated RFM-based CRM is suitable for strengthening SME marketing in a more targeted and measurable manner.